Global transformational leadership scale: cross-cultural adaptation of Indonesian sports science student context - Mahardika, I Made Sriundy; Blegur, Jusuf; Berliana, Berliana; Anaktototy, Jacob; Boleng, Lukas Maria; Arhesa, Sandra (International Journal of Evaluation and Research in Education (IJERE), 2024)
Transformational leadership has become an essential aspect of life skills integrated into a learning activity. At the same time, the tools for evaluating transformational leadership in the context of sports students in Indonesia still need to be improved. This study aims to adapt the global transformational leadership scale (GTLS) into the Indonesian version constructed from seven potential behaviors (vision, staff development, supportive, empowerment innovative, lead by example and charismatic). Testing content validity uses nine raters from various disciplines. Construct validity uses 297 students and concurrent validity by correlating GTLS scores with the leadership practices inventory (LPI). The data were analyzed using the Aiken formula, factor analysis, Pearson, and Cronbach's alpha with the help of the SPSS-AMOS. The result was that the seven adapted GTLS items met the Aiken validity parameter=0.74-0.96, construct validity (discriminant index=0.59-0.70; factor loading=0.63-0.77; p-value=0.000; RMR=0.013; GFI=0.961; TLI=0.952, CFI=0.968; RMSEA=0.080), concurrent validity (r=0.467), and reliability parameters=0.87. Thus, the Indonesian version of GTLS is valid and reliable for measuring transformational leadership in sports student culture. However, GTLS only facilitates members’ perceptions of their group leaders, so it is necessary to develop a GTLS scale oriented towards students perceiving their transformational leadership. These two data from different perspectives (peer and self-perception) enlarge the results of lecturers' comprehensive measurement, assessment, evaluation, and improvement of their students’ leadership.